2022
DOI: 10.3390/plants11101353
|View full text |Cite
|
Sign up to set email alerts
|

The Medicinal Halophyte Frankenia laevis L. (Sea Heath) Has In Vitro Antioxidant Activity, α-Glucosidase Inhibition, and Cytotoxicity towards Hepatocarcinoma Cells

Abstract: This work explored the medicinal halophyte Frankenia laevis L. (sea heath) as a potential source of bioactive natural products. In this sense, methanol and dichloromethane extracts were prepared from aerial organs containing flowers, leaves and stems, and were profiled for their chemical composition using high-performance liquid chromatography coupled with electrospray ionization mass spectrometry (HPLC-ESI-MS/MS). The extracts were evaluated for their in vitro antioxidant capacity using five complementary met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…ABTS scavenging capacity of SADE is similar to that of S. europea originating from Italy (ABTS = 15.1 mg TE/g) reported by Costa et al [ 49 ]. Halophyte plant extracts are characterized by promising in vitro antioxidant activities, as reported by many authors [ 19 , 22 , 50 ]. Phenolic acids such as ferulic acid, cinnamic acid, chlorogenic acid and coumaric acid were reported as the main phenolic compounds in many halophytes [ 18 , 37 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…ABTS scavenging capacity of SADE is similar to that of S. europea originating from Italy (ABTS = 15.1 mg TE/g) reported by Costa et al [ 49 ]. Halophyte plant extracts are characterized by promising in vitro antioxidant activities, as reported by many authors [ 19 , 22 , 50 ]. Phenolic acids such as ferulic acid, cinnamic acid, chlorogenic acid and coumaric acid were reported as the main phenolic compounds in many halophytes [ 18 , 37 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 88%
“…Many authors reported that the consumption of an HCD increases body weight and induces the accumulation of fat in adipose tissue. The accumulation of fat is the result of direct excess intake of a high-fat diet and/or the synthesis of fatty acids, mainly from carbohydrates [ 50 ]. The oral administration of SADE induced a decrease in body weight and adiposity index.…”
Section: Resultsmentioning
confidence: 99%
“…Usual therapeutic tools to prevent and/or ameliorate health conditions involve the inhibition of related key enzymes, as for example, α-glucosidase and α-amylase for diabetes (T2DM), cholinesterases (AChE, BChE) for Alzheimer’s disease and neurodegeneration, or tyrosinase for hyperpigmentation disorders [ 86 ]. Hence, efforts have been focused on identifying effective enzymatic inhibitors from natural sources [ 82 , 87 , 88 , 89 , 90 ]. In this sense, the enzyme inhibitory properties of extracts from sawgrass seeds were evaluated on the above-mentioned enzymes implicated with neurodegeneration (AChE and BChE), T2DM (α-glucosidase and α-amylase), and hyperpigmentation (tyrosinase), in view of their potential as source of phyto-therapeutic compounds and/or functional food ingredients ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…PTC techniques have greatly contributed to industry and agriculture in the last 60 years by exploiting the economic potential of medicinal and crop plants [ 3 ]. Research on halophytes is increasing and focuses mainly on its biochemical properties and cultivation [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The application of tissue culture refers only to a few species [ 13 , 14 , 15 , 16 , 17 , 18 ], but already yielded the optimization of cosmetic ingredients of high commercial value (CELTOSOME TM ) from sea fennel and sea holly ( Eryngium maritimum ) [ 19 ].…”
Section: In Vitro Plant Tissue Culturementioning
confidence: 99%